Experimental investigation of mechanical and durability performances of self-compacting concrete blended with bagasse ash, metakaolin, and glass fiber - Wagh, Monali; Waghe, Uday; Bahrami, Alireza; Ansari, Khalid; Özkılıç, Yasin Onuralp; Nikhade, Anshul (Frontiers in Materials, 2024)
This study investigated the effects of using bagasse ash (BA) and metakaolin (MK) together as substitutes for cement in self-compacting concrete (SCC), together with the addition of glass fiber (GF), on the physical and mechanical characteristics of concrete. Eighteen SCC mixes were created, each containing different proportions of BA (0%, 10%, 15%, and 20%), MK (0%, 10%, 15%, and 20%), and BA and MK collectively (10% + 5% and 10% + 10%) as cement replacements with and without 0.1% GF. Using the results of the slump flow, T500 slump flow, V-funnel, and L-box tests, the performance of fresh SCC was determined. Furthermore, this study evaluated the strength, durability, and microstructural properties of the SCC samples. The SCC mix blended with 10% BA and 5% MK revealed better flowability as the slump flow increased from 692 mm to 715 mm. A strong linear correlation was discovered between the slump flow values (mm) and V-funnel duration (sec) and blocking ratio (H2/H1) with R2 = 0.8876 and R2 = 0.8467, respectively. Of all test mixes, the SCC mix blended with 10% BA, 5% MK, and 0.1% GF (SCC1B10M5) demonstrated the highest degree of strength. At 56 days, the 10% BA, 5% MK, and 0.1 GF mix had 12.8%, 25.7%, and 22.2% higher compressive, flexural, and splitting tensile strengths than the control mix, respectively. SCC, combined with BA, MK, and GF, outperformed the control mix. After immersion in a 3% H2SO4 solution, the SCC mix having 10% BA, 5% MK, and 0.1% GF experienced a minimum reduction in weight loss and ultrasonic pulse velocity of 1.01% and 3.1%, respectively. Additionally, there was a decrease of 29.4% in the percentage of charges passed. The ideal composition was achieved by incorporating 10% BA, 5% MK, and 0.1% GF into the SCC mixture, resulting in a dense structure without any visible pores or cracks during the microstructural analysis.